The role of Guest-cards in developing “Slow Tourism” in Austria and Hungary - Bakucz, Márta; Horváth, Ádám; Bozóti, András (Marketing & Menedzsment, 2019)
AIM The aim of our study is to evaluate new types of discount card which support the purchase of goods or services in tourist destinations. METHODOLOGY We focus primarily on the spa sector and this is for several reasons. The importance of the sector in Hungary is such that it affords us a broader background and at least some choice of examples to assist our study. We also consider that the close relationship between spa- and slow tourism will show results and effects more clearly. We approach this by examining two Regions in Hungary (West and South Transdanubia) and the types of guest-card used there. Then we look more closely at specific tourist destinations - in Austria and in Hungary. MAIN FINDINGS Our study highlights an Austrian example (Bad Kleinkirchheim in Carinthia) of a high-quality guest-card, whose introduction is notable due to its bold approach to the concept. A somewhat similar card has now appeared in Hungary- perhaps not surprisingly, in the Balaton Holiday Region - and we have also had the opportunity to look at a further product introduced in Harkány, in South Transdanubia. We describe the principal features of the various products. RECOMMENDATIONS We then draw conclusions based on direct contact (largely by telephone) with senior responsible officials in the destinations.